2022
DOI: 10.1155/2022/9197369
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Amiodarone and Esmolol for Heart Rate and Cardiovascular Changes

Abstract: Objective. To probe into the effects of amiodarone and esmolol for heart rate disorders and myocardial infarction. Methods. 76 cases of cardiopathy in our hospital from July 2019 to October 2021 were analyzed for myocardial infarction. The control group applied amiodarone treatment. Blood pressure, treatment effect, adverse reactions, myocardial marker levels, electrocardiogram, and heart function indicators were compared. Results. There were no statistical differences in two groups of diastolic pressure ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%